Negociação e implementação de acordos de poluição transfronteiriça: o caso Brasil-Uruguai em relação à Termelétrica de Candiota (RS) - Rótulo Decuadra, Daniel Enrique (2003)
Research studies about international environmental negotiations between States in Latin America are not common. This thesis is about the process of negotiation and implementation of bilateral agreements between Brazil and Uruguay on the risk of transboundary air pollution risk produced by the coal-powered thermoelectrical facility Presidente Médici (UTPM)- at Candiota region. This process is analyzed from 1988 until 2002. First, this thesis explains why this negotiation was possible. Some different factors explain it: a good historical relationship and trust between these two countries; Brazilian environmental agencies interests to improve monitoring UTPM emissions; lack of better alternatives to a non agreement for the two constituencies: Brazil and Uruguay and contextual factors, like Southern Cone Common Market (Mercosul) and changes in environmental policy in Brazil also explain common interests in joint problem resolving. Both States obtained mutual gains outcomes from the agreement by developing 'joint-fact- finding' research and monitoring. This monitoring did not show that acid rain was coming to Uruguai from Brazil. Second, this thesis shows that institutional agreement weakness was not an implementation impediment. On the contrary, it allows Brazilian authorities to cooperate with Uruguayans developing acid rain monitoring in Candiota region and both improving their technology of air monitoring. Third, this research shows that the implementation process (1991-2002) produced some different results and impacts: it helped to develop environmental agencies institutional capacity both in Brazil and Uruguay; it made possible some changes at the power of environmental agencies to control UTPM; implementation impacts also pushed UTPM 'enforcement'. Environmental agencies put UTPM under pressure, and different kind of measures to improve environmental performance were took by the firm. Finally, this thesis shows that implementation process was not finished because political interest´s about Candiota pollution declined at the public agenda in both countries: Brazil and Uruguay. Discussion on the problem became only scientific